Internalization of Social Media Adab Material in Grade XI PAI Learning at SMK NU Pamotan - Elisatun Khasanah; Ana Rahmawati (LP2M STIT Palapa Nusantara, 2025)
This study addresses the gap in research concerning the internalization of adab values through social media in Islamic Religious Education (IRE) within classroom settings, highlighting its significance for character development in the digital age. The purpose of this study is to analyze the strategies employed by Islamic Education teachers in internalizing adab values via social media, as well as to assess students' responses and behaviors related to these strategies. Employing a descriptive qualitative methodology, the research focuses on PAI teachers and grade XI students at SMK NU Pamotan. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, incorporating triangulation of techniques and sources to ensure data validity. Findings indicate that the internalization of social media adab values is facilitated through a contextual approach, aligning with students' lived experiences, exemplified by real case discussions, teacher modeling, and active student participation. Key values such as responsibility, courtesy, and honesty were effectively instilled, leading to the development of new social media habits among students. In conclusion, IRE that prioritizes the internalization of adab values significantly influences students' attitudes towards responsible and wise social media use. It is essential for PAI teachers to continuously innovate adaptive learning approaches that meet the evolving dynamics of social media usage, while support from the school and family environment remains crucial for successful character development.